EXPERIMENTAL CONSTRAINTS ON DEGASSING OF MAGMA: ISOTHERMAL BUBBLE GROWTH DURING CONTINUOUS DECOMPRESSION FROM HIGH PRESSURE - Gardner J.E.; Hilton M.; Carroll M.R. (My University, 1999)
Numerical models predict that rapid ascent of hydrous magma can lead to supersaturation of dissolved volatile constituents, possibly leading to explosive eruption. We have performed controlled decompression experiments to investigate the ascent rates required to maintain bubble-melt equilibrium. High-silica rhyolitic melts were saturated with water at 200 MPa and 825°C, decompressed to lower pressures at constant rates of 0.025, 0.25, 0.5, and 1.0 MPa s-1, and then rapidly quenched isobarically. Other samples were saturated with water over the pressure range investigated to determine equilibrium water solubility in order to quantify degassing efficiency during decompression. At a decompression rate of 0.025 MPa s-1, melt-vapor equilibrium was maintained over the entire pressure range examined: 200 to 17.5 MPa. A single bubble nucleation event occurred in response to decompression, and quenched bubble sizes can be modeled by a equilibrium bubble growth model that takes into account the number density of bubbles. At decompression rates of 0.25, 0.5, and 1.0 MPa s-1, rhyolitic melts could not degas in equilibrium when pressure decreased from 200 MPa to 140 MPa, and water supersaturation (ΔP) in the melt reached up to 60 MPa, with higher values at faster decompression rates. Further pressure release resulted in near equilibrium degassing and ΔP dropped significantly. In each case, ΔP decreased when bubbles exceeded 10 vol.%. A single, heterogeneous bubble nucleation event occurred in each experiment when ΔP<20 MPa; no other bubbles nucleated despite ΔP reaching 60 MPa, which is probably too low to trigger homogeneous nucleation. Compared to estimates for magma decompression rates during lava dome eruptions, our results indicate that magmas can degas efficiently throughout their ascent to the surface. In explosive eruptions, decompression rates may exceed those of this study and hence melts may become supersaturated with water. Such fast decompressions are expected, however, only when magma is highly vesicular, which would aid approach to equilibrium degassing.
Keywords: MAGMAS; DEGASSING; DECOMPRESSION; P-T CONDITIONS; EXPERIMENTAL STUDIES